2007
DOI: 10.1111/j.1742-7843.2007.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan Toxicity to Human Blood Cells in vitro: Relationship between Various Biomarkers

Abstract: Toxic effects of the antineoplastic drug irinotecan on human blood cells at concentrations of 9.0 µ g/ml and 4.6 µ g/ml were evaluated in vitro . Using the alkaline and neutral comet assay significantly increased levels of primary DNA damage in lymphocytes were detected. The induction of apoptosis/necrosis, as determined by a fluorescent assay, was also notably increased. Cytogenetic outcomes of the treatment were assessed by the analysis of structural chromosome aberrations and fluorescence in situ hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
4
15
1
Order By: Relevance
“…It is reasonable to assume that mice surviving more than 50 days eliminated Ehrlich ascites tumour cells because of the combined activity of irinotecan and the beneficial effects of flavonoids, which, based on our results, possess immunomodulating activity. Immunomodulating activity of these compounds was also reported earlier [30–33].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is reasonable to assume that mice surviving more than 50 days eliminated Ehrlich ascites tumour cells because of the combined activity of irinotecan and the beneficial effects of flavonoids, which, based on our results, possess immunomodulating activity. Immunomodulating activity of these compounds was also reported earlier [30–33].…”
Section: Discussionsupporting
confidence: 75%
“…As one of the most frequently used anti‐tumour drugs, it is particularly active in the treatment of gastrointestinal and pulmonary malignancies [1–4]. However, treatment with irinotecan is often accompanied by side effects, especially those related with cholinergic effects in the gastrointestinal tract and haematological toxicity [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aydemir and Bilaloglu (33) found an increase in MN frequency in the bone marrow cells of mice treated with topotecan (an analogue of irinotecan). Kopjar et al (14) found a signifi cant increase in the MN frequency in human lymphocytes even at a lower dose of 4.6 µg mL -1 of irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“…al. (14), tested the toxicity of 4.6 µg mL -1 and 9 µg mL -1 irinotecan on human blood cells, and also reported higher cytotoxicity at a lower dose of the drug. The other possible explanation for our results could be the apoptotic elimination of cells whose DNA was not repaired.…”
Section: Discussionmentioning
confidence: 99%